Targeting mitochondria in dermatological therapy: beyond oxidative damage and skin aging. (4th March 2022) - Wikramanayake, Tongyu C; Chéret, Jérémy; Sevilla, Alec; Birch-Machin, Mark; Paus, Ralf
ABSTRACT: Introduction: The analysis of the role of the mitochondria in oxidative damage and skin aging has been a significant aspect of dermatological research. Mitochondria generate most reactive oxygen species (ROS) which, in excess, are cytotoxic and DNA-damaging and promote (photo-)aging. However, ROS also possesses key physiological and regulatory functions and mitochondrial dysfunction is prominent in several not primarily senescence-associated skin diseases and skin cancers. Although many standard dermatotherapeutics modulate mitochondrial function, dermatological therapy rarely targets the mitochondria. Accordingly, there is a rationale for 'mitochondrial dermatology'-based approaches to be applied to therapeutic research, as we advocate here. Areas covered: This paper examines the functions of mitochondria in cutaneous physiology beyond energy (ATP) and ROS production. Keratinocyte differentiation and epidermal barrier maintenance, appendage morphogenesis and homeostasis, photoaging and skin cancer are considered. Based on related PubMed search results, the paper evaluates thyroid hormones, glucocorticoids, Vitamin D3 derivatives, retinoids, cannabinoid receptor agonists, PPARγ agonists, thyrotropin, and thyrotropin-releasing hormone as instructive lead compounds. Moreover, the mitochondrial protein MPZL3 as a promising new drug target for future 'mitochondrial dermatology' is highlighted. Expert opinion: Future dermatological therapeutic research should have a mitochondrial medicine emphasis. Focusing on selected lead agents, protein targets, in silico drug design, and model diseases will fertilize a mito-centric approach.